Histological Alterations of the Duodenum Induced by Sleeping Pills - Krisnasari, Alfian Silvia; Sugianto, Yohanes (Jurnal Biologi Tropis, 2025)
In Indonesia, sleep disorders, including those triggered by fatigue, have a relatively high prevalence. Data indicate that about 10% of the population, or approximately 28 million people, experience insomnia, with findings from the Indonesia Family Life Survey (IFLS-5) revealing that 33.3% suffer from mild insomnia, 11% from clinical insomnia, and 1% of respondents use sleeping pills. One type of sleeping pill classified as a narcotic and psychotropic substance is Diazepam (Psychotropic IV). This study aimed to investigate changes in the digestive system, particularly in the duodenum, as the organ responsible for absorbing various substances entering the body. The research used 12 rats divided into four groups: a control group (1% Polyethylene Glycol 1000) and three diazepam-treated groups (P1, P2, P3) with concentrations of 62.25, 83, and 124.5 mg/kg BW, respectively. Treatments were administered for 28 days. Afterward, the rats were euthanized, and the duodenum was necropsied. Specimens were prepared using the paraffin method and stained with hematoxylin-eosin. Histological structures were examined microscopically and scored. Observed histological damage included glandular dilation, edema, pyknosis, congestion, epithelial erosion, and neutrophil infiltration. Diazepam acts by enhancing the effect of the neurotransmitter GABA in the central nervous system, producing sedative and muscle relaxant effects; however, this muscle relaxation can also affect smooth muscles in the gastrointestinal tract, reducing intestinal motility.